You are what you eat, whenever or wherever you eat it: an integrative analysis of fish food habits in Canadian and U.S.A. waters - A. Bundy; J. S. Link; B. E. Smith; A. M. Cook (Journal of Fish Biology, 2011)
The degree to which fish diet differs by season and area, particularly over broad scales, was examined for the first time in temperate, contiguous north‐west Atlantic Ocean waters by comparing food habit data for 10 species of fishes collected concurrently during the spring and autumn surveys in the U.S.A. (Gulf of Maine proper and Georges Bank) and in the summer survey in Canada (western Scotian Shelf and Bay of Fundy). For most species, there was a general concurrence among the three seasons and four areas: summer diets had the same dominant prey items as spring and autumn diets. Although a suite of multivariate analyses did elucidate some differences in specific proportions of the diet for these species across seasons and areas, the main prey did not substantially change for most of these species. These results suggest that there are (1) minimal differences in diet across season for these species at these taxonomic resolutions, (2) there are minimal differences in diet geographically for these species and (3) differences across species, as expected, are important. Many fisheries ecosystem and multispecies models are dependent on food habit data, where resolving seasonal and spatial differences in diet remains an important consideration; however, the present work implies that amalgamated estimates of diet from seasonal surveys may be a reasonable approach when no finer seasonal resolution exists, as long as due diligence is exercised.